Enalapril Maleate Has Cytotoxıc Effect in Hl 60 Leukemic Cells by Altering Stat Signaling Pathway - Şahin, Fahri; Baran, Yusuf; Purçlutepe, Özlem; Kiper, Hatice Demet; Tezcanlı, Burçin; Selvi, Nur; Biray Avcı, Çığır; Baran, Yusuf; Saydam, Güray (Ferrata Storti Foundation, 2012)
[No abstract available]